CLUSTER ANALYSIS OF FINANCIAL BEHAVIORS AND PREFERENCES AMONG THE BOTTOM OF THE PYRAMID GROUP - Saraswati, Dewi; Kusumaningrum, Dian (Jurnal Manajemen dan Kewirausahaan, 2019)
This study investigates the financial behavior and preferences of the bottom of the pyramid (BOP) group, and thus, contributes to the financial inclusion demand-side literature. A survey of 100 households was conducted. A cluster analysis was used to analyze the data and portray the characteristics of the BOP. Further analysis was conducted using chi-square and ANOVA tests. The results reveal three sub-groups within the BOP which consists of the very low, low, and medium. Financial behaviors are found to be indifferent among the sub-groups, except for savings allocations and financial planning. Households with a better economic condition are found to have a higher attention to use banking services. The financial literacy category indicates different attitudes in conducting long-term financial planning and service preferences. This result implies that financial literacy and adequate financial products are beneficial towards the financial inclusion of the BOP group.